Mandatory treatment for methamphetamine use in Australia - Mathew Coleman; Kelly Ridley; Michael Christmass (BMC, 2021)
Abstract Background In 2016, following a flurry of government inquiries and taskforces including calls for mandatory treatment regimes, the Australian community nominated methamphetamine as the drug most likely to be associated as a problem substance. Mandatory treatment for alcohol and other drug problems in Australia consists of broadly two mechanisms compelling a person into treatment: involuntary treatment or civil commitment regimes; and coercive treatment regimes, usually associated with the criminal justice system. This paper aims to provide a review of the evidence for mandatory treatment regimes for people who use methamphetamines. Methods Using a narrative review methodology, a comprehensive literature and citation search was conducted. Five hundred two search results were obtained resulting in 41 papers that had cited works of interest. Results Small, but robust results were found with coercive treatment programs in the criminal justice system. The evidence of these programs specifically with methamphetamine use disorders is even less promising. Systematic reviews of mandatory drug treatment regimes have consistently demonstrated limited, if any, benefit for civil commitment programs. Despite the growing popular enthusiasm for mandatory drug treatment programs, significant clinical and ethical challenges arise including determining decision making capacity in people with substance use disorders, the impact of self determination and motivation in drug treatment, current treatment effectiveness, cost effectiveness and unintended treatment harms associated with mandatory programs. Conclusion The challenge for legislators, service providers and clinicians when considering mandatory treatment for methamphetamines is to proportionately balance the issue of human rights with effectiveness, safety, range and accessibility of both existing and novel mandatory treatment approaches.